APLIKASI CAMPURAN BIOURIN DENGAN AGEN PENGENDALI HAYATI UNTUK MENINGKATKAN PRODUKTIVITAS TANAMAN SAWI HIJAU (Brassica rapa Var. Parachinensis L.) - Hendrawati, I Gusti Agung Oka; Sudana, I Made; Wirya, G N Alit Susanta (Journal of Agricultural Science and Biotechnology, 2015)
The research was conducted in Pancasari Village, District Sukasada, Buleleng regency from July to November 2013. Purpose of this study was to determine the effectiveness of combination of bio urine with biological control agent in improving productivity and control pests and diseases in greens mustard plants. This study used a randomized block design (RBD) with one bio urine treatment factors, namely bio urine added crushed with Balinese spices ( base genep ), crushed mimba leaves, crushed leaves of the sour sop, chopped tobacco leaves, Bacillus thuringiensis , Trichoderma viride , Beauveria sp., bio urine without a mixture of biological control agents, chemical pesticides and is equipped with controls (just doused with water). The results of this study showed that bio urine with combination of the biological control agent variables significantly application of affect to plant height, leaf area index, chlorophyll quantity, above-ground fresh weight, fresh roots weight, above-ground dry weight, root dry weight, the percentage of club root, number of leaves damaged, the intensity of leaf damage and abundance imago of Liriomyza sp. Based on these results of this research it can be concluded that the treatment bio urine can control pest grasshoppers, control club root disease and improve productivity of greens mustard.
Keywords: bio urine, green mustard, productivity, biological control agents